Strategies of expansion for electric power systems based on hydroelectric plants in the context of climate change: case of analysis of Colombia (2020)
The phenomena of climatic variability such as El Niño affect the expansion planning of electricity supply systems with hydroelectric power plants due to the uncertainty presented in the variables of rainfall patterns, temperature, wind, solar radiation changes, among others. The El Niño affects the electricity generation in Colombia, Venezuela and northwestern Brazil due to severe droughts that reduce water flows in rivers and water volume in dams. While in Peru, Paraguay, Bolivia, Uruguay, Argentina and southern Brazil, causes heavy rains that lead to an increase in reservoirs. Recent findings provide sufficient evidence on how climate change modifies the patterns of duration, frequency and intensity of El Niño and therefore will introduce additional uncertainties to the expansion planning of electricity generation systems in countries that uses predominantly hydroelectric power. The vulnerability of electricity supply systems with a significant participation of hydroelectric power plants in Colombia, Brazil, Ecuador, Peru, Panama, Canada, Norway, Costa Rica and New Zealand is associated with fluctuations in the availability of water resources. This document aims to analyze the current plans for the expansion of electric power generation systems by the aforementioned countries in the context of climate change in medium and long term. Additionally, this document provides a detailed analysis of the situation of electricity supply systems in Colombia